Analysis of the Automotive Ignition System for Various Conditions - Matej Kucera; Milan Sebok; Matej Kubis; Daniel Korenciak; Miroslav Gutten (Communications - Scientific letters of the University of Zilina, 2020)
Paper presents diagnostic analysis of automotive ignition system for various working and adverse conditions in laboratory. Description and importance of basic diagnostics of automotive ignition system are examined in the first part of the paper. In the second the focus is placed on the basic principles and solution of the spark plug model. The test laboratory device is proposed in the following and the specialized measurements were executed by the proposed measurement system. The faults were simulated by application of oil and gasoline between the electrodes and failing by the driver to make the ignition contact on the spark plug.